Studi Literatur: Asupan Gizi dan Kejadian Anemia Remaja Putri Usia 14-16 Tahun - Niken Mega Yustika; Lisa Purbawaning; Suprapti Suprapti (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2020)
Nutritional problems that occur in Indonesia, including anemia due to lack of nutrients, namely lack of carbohydrates, lack of fat, lack of protein, lack of vitamins and minerals. Anemia is usually suffered by adolescent girls because during their growth period they need higher nutrients, both micronutrients and macronutrients. This study aims to identify the relationship between nutrient intake and the incidence of anemia in adolescent girls aged 14-16 years through a literature review. The method used is a literature study obtained from Pubmed and Google Schoolar. The results showed that one journal in the study explained that there was a relationship between nutritional intake and anemia, there was one journal that explained that there was a relationship between nutritional intake, namely protein, iron, but there was no relationship between vitamin C intake and the incidence of anemia. There is one journal that shows there is a relationship between nutrient intake, namely carbohydrates, iron and vitamin C, but there is no relationship between protein intake and the incidence of anemia. There are 4 journals that show there is no relationship between nutrient intake and the incidence of anemia in adolescent girls. The conclusion of a small number of journals states that nutritional intake in adolescent girls aged 14-16 years is associated with the occurrence of anemia in adolescent girls. Keywords: Nutrition, Anemia, Teenage girl